Prezentacja badań niematerialnego dziedzictwa kulturowego w Muzeum Narodowym Rolnictwa w Szreniawie - Jełowicki, Arkadiusz (Zbiór Wiadomości do Antropologii Muzealnej, 2019)
This text will discuss the activities of the National Museum of Agriculture and Food Industry in Szreniawa (abbreviated to the Museum in Szreniawa) in the field of research, documentation of intangible cultural heritage and the dissemination of knowledge about it. This is only a presentation of findings which in the future may become the basis for deeper analysis or broader synthesis. The research mainly focused on the role the facilities play or are to play in the museum. Today, it is important to classify and present various undertakings of this institution.